2014
DOI: 10.1002/j.2161-007x.2014.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining Spirituality and Sense of Calling in Counseling Students

Abstract: This study explored the link between counseling students' spiritual well-being and sense of calling to the profession. A final sample of 415 counseling students demonstrated significant spiritual well-being (religious and existential) and a strong sense of calling to the counseling profession. Results also indicated that spiritual well-being was predictive of students' sense of calling to the profession. Implications for counselor training are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…A study on a mostly Christian sample of employees found perceiving and seeking a calling to be associated with higher levels of religious/spiritual importance (Ponton et al, 2014). Calling has also been linked to spirituality among counselors and social workers (Hall et al, 2014;Hirsbrunner et al, 2012). Thus, we hypothesized that there would be higher rates of presence of, search for, and living a calling among (1) religiously affiliated individuals (irrespective of tradition) compared to individuals with no religious affiliation and (2) those who place greater relative importance on God or spirituality.…”
Section: Research On Prevalence and Demographic Differencesmentioning
confidence: 99%
“…A study on a mostly Christian sample of employees found perceiving and seeking a calling to be associated with higher levels of religious/spiritual importance (Ponton et al, 2014). Calling has also been linked to spirituality among counselors and social workers (Hall et al, 2014;Hirsbrunner et al, 2012). Thus, we hypothesized that there would be higher rates of presence of, search for, and living a calling among (1) religiously affiliated individuals (irrespective of tradition) compared to individuals with no religious affiliation and (2) those who place greater relative importance on God or spirituality.…”
Section: Research On Prevalence and Demographic Differencesmentioning
confidence: 99%
“…They reported that participants' basic individual values emphasized benevolence, selfdirection, and achievement, whereas the measured work values emphasized lifestyle, supervision, and achievement. Additionally, Hall et al (2014) used an assessment with counselor education trainees that measured calling to a profession through the concepts of intrinsic motivation and meaning. Their results suggested that counselor education trainees are drawn to an occupation that offers them a strong sense of purpose and meaning.…”
Section: Work Valuesmentioning
confidence: 99%
“…In addition, the literature is replete with findings indicating the importance of providing planned, consistent, and effective training to counseling students on issues of spirituality (Cashwell & Young, ; Henriksen, Polonyi, Bornsheuer‐Boswell, Greger, & Watts, ; Kimbel & Schellenberg, ; Myers & Williard, ; Pate & High, ; Reiner & Dobmeier, ). Given that the cornerstone of counseling is client wellness and that client wellness is profoundly affected by spiritual and religious belief systems, it is an ethical and culturally sensitive stance to ensure that counselor education and practices explore these natural areas of human development, contemporarily named the “fifth force” (Sandhu as cited in Stanard et al, , p. 204) in counseling (ACA, ; ASERVIC, ; Hall, Burkholder, & Sterner, ; Kimbel & Schellenberg, ; Myers & Sweeney, ).…”
Section: The Critical Nature Of Spirituality In Holistic Wellnessmentioning
confidence: 99%
“…Although the counseling literature and the profession have endorsed addressing spiritual and religious issues in counseling, the integration of these issues in counselor education programs is inconsistent. In addition, through a Spirituality and Religion core curriculum area, the correlation between spirituality and wellness counseling can be solidified (Anandarajah & Hight, ; Hall et al, ; Hirsbrunner, Loeffler, & Rompf, ; van Asselt & Senstock, ).…”
Section: Recommendationsmentioning
confidence: 99%